The long-term effectiveness and acceptability of the retailer-led removal of unhealthy drinks from display in a self-service café. Issue 10 (13th July 2020) - Ryan, Angela; Huse, Oliver; Blake, Miranda R; Boelsen-Robinson, Tara; Noble, Kia; Peeters, Anna
Abstract: Objective: In 2015, beverages were removed from display at a self-service café within a major health service, resulting in fewer purchases of unhealthy beverages. This initiative was continued following initial evaluation of the results. The current study aimed to determine customer acceptability of the initiative, and whether healthier purchases had continued, at 18 months following implementation. Design: Drinks were categorised as 'green' (best choices), 'amber' (choose carefully) and 'red' (limit), based on the state government nutrient profiling system, for intervention and analysis purposes. In 2015, unhealthy 'red' drinks were removed from display. In 2017, weekly beverage sales were counted, through stock-taking, for 6 weeks, and customer surveys were conducted over 2 days. Setting: A café located within a major Victorian health service. Participants: Café customers (hospital staff, patients and visitors). Results: Eighteen months after the implementation of the initiative, the proportion of 'red' beverages sold was 7 % of total drink sales (compared with 33 % before the removal of unhealthy beverages from display in 2015 ( P < 0·001), and 10 % immediately following the removal of unhealthy beverages from display). Customer surveys revealed high levels of acceptability for the initiative and low levels of awareness of the initiative. Conclusions: The removal of unhealthy beverages from display can result in customers making healthier purchases, and this appears to continue over the long-term. Such interventions have the potential to contribute to the sustained shift in population purchases and consumption needed to make meaningful improvements to population health.